A case study on the performance of approval of Proton Commerce Sdn Bhd’s hire purchase loan towards CIMB business process / Muhammad Hakeem Ab Rahman - Ab Rahman, Muhammad Hakeem (Faculty of Business and Management, Universiti Teknologi MARA, 2009)
This study was conducted to find the performance of approval of Proton Commerce Sdn.Bhd hire purchase loan towards CIMB business process. This study is emphasizes on how Proton Commerce Sdn Bhd to overcome the CIMB business process. The objectives of this study are to increase and make the performance of hire purchase loan is better than before. The issue for this study is the problem facing by Proton Commerce Sdn Bhd staff in order to achieve the hire purchase loan approval. The finding will discuss on total submission, approval and rejection application with the alternatives taken by Proton Commerce Sdn Bhd in order to overcome CIMB business process. The gap identification will discuss whether the company can achieve the sales target. As a conclusion, it will determine whether CIMB business process may affect the company in order to grab more customers and a good relationship and co-operation both parties may affect the hire purchase loan approval.